Struktur Penyajian Diki Asrakal dalam Acara Ptang Balimau di Kesultanan Nopugho Desa Indrapura Kecamatan Pancung Soal, Pesisir Selatan - Revo Bramasta; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2023)
This study aims to find out and describe how the Presentation Structure of Diki Asrakal in the Ptang Balimau Event in the Nopugho Sultanate, Indrapura Village, Pancung District, South Coast Regency. This type of research is qualitative research using descriptive methods of analysis. The instrument is the researcher himself and uses several additional instruments such as stationery and mobile phones. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps to analyze data are to collect data, describe data and infer data. The results showed that Diki Asrakal's art was preserved from the past until now, although to continue the art of Diki Asrakal requires harder efforts because Diki Asrakal's art is only played by men.Diki Asrakal has from several sides regressed and on the other hand has also made progress. The decline is due to the small number of enthusiasts to learn Diki Asrakal art from among young people who are rarely interested in traditional music, especially since Diki Asrakal art is only played by men, the progress has been that there have been several groups that have raised the art of Diki Asrakal both in the local nagari and outside the local nagari, especially the studios in Indrapura village. So in the performances Diki Asrakal always goes to the local traditional rituals where the presentation structure is led by the Sultan of Indrapura (Rusdal Inayatsah).